y+3=2x+3

Simple and best practice solution for y+3=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y+3=2x+3 equation:


Simplifying
y + 3 = 2x + 3

Reorder the terms:
3 + y = 2x + 3

Reorder the terms:
3 + y = 3 + 2x

Add '-3' to each side of the equation.
3 + -3 + y = 3 + -3 + 2x

Combine like terms: 3 + -3 = 0
0 + y = 3 + -3 + 2x
y = 3 + -3 + 2x

Combine like terms: 3 + -3 = 0
y = 0 + 2x
y = 2x

Solving
y = 2x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 2x

See similar equations:

| 23*7-45= | | 3/10x40 | | -x=-37/8 | | 71/5 | | 2x+9y=70 | | 6+2x-7x=9 | | 9x+48=6x-12 | | 6Y=20-5X | | 6r-10=-4+7r | | (5/14)÷(2/7) | | 8v+39=-3v-7(8+4) | | 4x^2-15x-x=0 | | x^4(1/9x^3)(6x^4 | | 8xsquared+18x+10=0 | | 6x+5x=17 | | 5*3+2*5= | | (7x+4)*(-4x-5)= | | 3/10×40 | | 1/2b=-3 | | 4y+1=y-3 | | 10x^2+20x-150=0 | | 20/7n-5/3n | | 10x+2y=7 | | 21=7/8x | | 7(-x-4)=-2x-33 | | p-7.2=-3.43 | | (2x^2y+y^2)dy=(-4xy-1)dx | | x^2+y^2+2xy+2x+2y-3=0 | | x+(x+4)=70 | | y-3=6/1(x-3) | | (-3/20)-1=(6/x) | | x^2+y^2+2xy+2y+2x+2y-3=0 |

Equations solver categories